2012
DOI: 10.1097/med.0b013e3283565bb2
|View full text |Cite
|
Sign up to set email alerts
|

Iodine-induced thyroid dysfunction

Abstract: Purpose of review To summarize the mechanisms of iodine-induced hypothyroidism and hyperthyroidism, identify the risk factors for thyroid dysfunction following an iodine load, and summarize the major sources of excess iodine exposure. Recent findings Excess iodine is generally well tolerated, but individuals with underlying thyroid disease or other risk factors may be susceptible to iodine-induced thyroid dysfunction following acute or chronic exposure. Sources of increased iodine exposure include the global… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
89
0
9

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 135 publications
(99 citation statements)
references
References 52 publications
1
89
0
9
Order By: Relevance
“…Early AIH may be present in 10% to 20% of patients treated with amiodarone, whereas the incidence with long-term treatment is often lower, from 5% to 10%. AIH is noted to be more frequent in iodine-sufficient areas of the world, 18 and the presence of thyroid autoantibodies is associated with an increased likelihood of developing AIH. There is also an understanding that amiodarone may hasten the pathogenesis of Hashimoto thyroiditis.…”
mentioning
confidence: 99%
“…Early AIH may be present in 10% to 20% of patients treated with amiodarone, whereas the incidence with long-term treatment is often lower, from 5% to 10%. AIH is noted to be more frequent in iodine-sufficient areas of the world, 18 and the presence of thyroid autoantibodies is associated with an increased likelihood of developing AIH. There is also an understanding that amiodarone may hasten the pathogenesis of Hashimoto thyroiditis.…”
mentioning
confidence: 99%
“…These collective data bear great clinical relevance given the known adverse effects of hyperthyroidism on multiple organ systems (i.e., bone, neuropsychiatric) 16 particularly the cardiovascular system (e.g., atrial fibrillation, high-output heart failure, angina, and possibly greater cardiovascular mortality). 17,18 Although untested, it has been suggested that prophylactic treatment with methimazole or perchlorate may be warranted in high-risk patients in advance of anticipated iodide exposure such as elective ICM-based procedures; 2,19,20 further studies are needed to evaluate the safety and effectiveness of this approach.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 However, it has long been recognized that acute or chronic exposure to excess iodine from non-ICM sources (e.g., medications, disinfectants, diet) may result in thyrotoxicosis in some patients. 2,12 Iodine-induced hyperthyroidism (Jöd Basedow phenomenon) has typically been described in patients with latent nodular or diffuse goiter or Graves' disease residing in areas of iodine deficiency who remain clinically euthyroid until iodine repletion. 1,13,14 However, iodine-induced hyperthyroidism has also been observed in patients without pre-existing thyroid disease residing in iodine-replete regions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations